Analysis of the Effect of Field Trip Learning on Elementary School Students' Understanding of Citizenship - Cahyani, Yulia (International Journal of Students Education, 2024)
Education is one of the important things for human life. With education, humans can gain various knowledge and develop their competence. The main purpose of the literature review research is to produce an analysis of the influence of field trip learning on elementary school students' understanding of citizenship. In the modern world of education, the focus is on improving students' skills and creating quality individuals, as well as enriching students' lives through various fields such as religion, art, creativity, communication, education, and others. Students can get skills that match their abilities. Education allows people to access information easily and has a good influence on their lives. The research in this article was written using the literature review method. Literature review is a research method that is carried out by identifying, evaluating, and synthesizing previous works such as systematically and explicitly. Previous works that are collected and analyzed are in the form of national and international journals. The results of the study show that the use of the field trip method can make it easier for students to understand and concentrate on the material and create a more enjoyable learning atmosphere, as well as provide stronger, imaginative, creative and greater opportunities to develop.